Long-Term Benzodiazepine Use and Mortality: Are we Doing the Right Studies? - Kalum Amarasuriya, Umesh; R. Myles, Puja; David Sanders, Robert (Current Drug Safety, 2012)
Benzodiazepines are World Health Organisation essential medicines used in the treatment of alcohol withdrawal, anaesthesia, sedation, anxiolysis, behavioural disturbance, epilepsy, insomnia, palliative care, and muscle spasm. Despite their widespread use concerns remain over their long-term safety through both neuronal and non-neuronal effects. We conducted a systematic review to identify vulnerable populations of patients who may be at increased risk of harm from benzodiazepines. We identified three potentially “at risk” groups of patients, those with renal disease, lung disease and those recently hospitalised. However methodological limitations including selection bias, vague descriptors of benzodiazepine use and inappropriate grouping together of benzodiazepines with other medications, precluded definitive conclusions. Future studies should concentrate on these groups to identify the long-term safety of benzodiazepines in these patient groups.
Keywords: mortality